Hydrothermal venting and mineralization in the crater of Kick'em Jenny submarine volcano, Grenada (Lesser Antilles). (20th March 2016) - Carey, Steven; Olsen, Rene; Bell, Katherine L.C.; Ballard, Robert; Dondin, Frederic; Roman, Chris; Smart, Clara; Lilley, Marvin; Lupton, John; Seibel, Brad; Cornell, Winton; Moyer, Craig
Abstract: Kick'em Jenny is a frequently erupting, shallow submarine volcano located 7.5 km off the northern coast of Grenada in the Lesser Antilles subduction zone. Focused and diffuse hydrothermal venting is taking place mainly within a small (∼70 × 110 m) depression within the 300 m diameter crater of the volcano at depths of about 265 m. Much of the crater is blanketed with a layer of fine‐grained tephra that has undergone hydrothermal alteration. Clear fluids and gas are being discharged near the center of the depression from mound‐like vents at a maximum temperature of 180°C. The gas consists of 93–96% CO2 with trace amounts of methane and hydrogen. Gas flux measurements of individual bubble streams range from 10 to 100 kg of CO2 per day. Diffuse venting with temperatures 5–35°C above ambient occurs throughout the depression and over large areas of the main crater. These zones are colonized by reddish‐yellow bacteria with the production of Fe‐oxyhydroxides as surface coatings, fragile spires up to several meters in height, and elongated mounds up to tens of centimeters thick. A high‐resolution photomosaic of the inner crater depression shows fluid flow patterns descending the sides of the depression toward the crater floor. We suggest that the negatively buoyant fluid flow is the result of phase separation of hydrothermal fluids at Kick'em Jenny generating a dense saline component that does not rise despite its elevated temperature. Key Points: Hydrothermal system of Kick'em Jenny explored using remotely operated vehicles Multiple lines of evidence for phase separation of hydrothermal fluids Mineralization dominated by deposition of iron‐oxyhydroxides